EFFECT OF CATHODE AND ANODE SEAWATER ELECTROLYSIS ON EXHAUST EMISSIONS OF DIESEL ENGINE - Agung Sudrajad; Mekro Permana Pinem; Sunardi Sunardi; Muhammad Zulfadly (Trends in Mechanical Engineering Research, 2026)
The objective of research is determining the effect of seawater electrolysis on emission levels on exhaust gases from diesel engine. The research was examined at the Energy Conversion Laboratory, Department of Mechanical Engineering, Faculty of Engineering, Sultan Ageng Tirtayasa University. The experimental are focused on emissions of carbon monoxide (CO), Carbon Dioxide (C ), and Hydrocarbons (HC) from diesel engine. The research was conducted by diesel engine with engine speed of 1200 rpm, 1600 rpm, and 2000 rpm. The results show that of the average decrease of CO is 51.73% in the anode process and 22.73% in the cathode process. Moreover, emissions of C is 17% in the anode and 10.7% in the cathode. Also, an average decrease of HC is 31.3% in the cathode process and 26.1% in the anode process.